On some qualitative properties of monotone linear extensions of dynamical systems - Grechko, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We study monotone linear extensions of dynamical systems. The problem of existence of invariant manifoldsand exponential separation is investigated for linear extensions on vector bundles that preserve the orderstructure. We also study the relationship between the monotonicity of linear extensions and the existence ofbounded solutions of inhomogeneous linear extensions (weak regularity, quasiregularity).